Major depression associated with a levonorgestrel-releasing intrauterine system mimicking frontotemporal dementia: a case report - Valencia-Cifuentes, Valeria; Cañas, Carlos A.; Rivas, Juan Carlos (Frontiers in Psychiatry, 2023)
This case illustrates the adverse cognitive and affective effects associated with the use of an intrauterine hormonal contraceptive, which could be confused with symptoms of early-onset dementia. We present a case of a 42-year-old woman diagnosed with seronegative spondyloarthropathy who subsequently developed anxiety and depressive symptoms after the implantation of a levonorgestrel-releasing intrauterine system (LNG-IUS). Three years later, she began to experience memory and attentional failures, refractory pain, and severe depression. The progression of psychiatric symptoms led to a diagnosis of bipolar affective disorder and treatment with antidepressants and anxiolytics. Due to cognitive and psychiatric symptoms, autoimmune encephalitis was considered, but no improvement was shown with treatment. Early-onset dementia was suspected, and a brain PET scan revealed frontal lobe hypometabolism. An adverse effect of LNG-IUS was considered; after its removal, mood and cognitive function improvements were observed. This case report emphasizes the importance of considering organic causes of unexplained psychiatric manifestations and highlights the potential impact of hormonal interventions on mental health.